Deferred action: Theoretical model of process architecture design for emergent business processes - Nandish V. Patel (International Journal of Business Science & Applied Management (IJBSAM), 2007)
E-Business modelling and ebusiness systems development assumes fixed company resources, structures, and business processes. Empirical and theoretical evidence suggests that company resources and structures are emergent rather than fixed. Planning business activity in emergent contexts requires flexible ebusiness models based on better management theories and models. This paper builds and proposes a theoretical model of ebusiness systems capable of catering for emergent factors that affect business processes. Drawing on development of theories of the "action and design" class the Theory of Deferred Action is invoked as the base theory for the theoretical model. A theoretical model of flexible process architecture is presented by identifying its core components and their relationships, and then illustrated with exemplar flexible process architectures capable of responding to emergent factors. Managerial implications of the model are considered and the model's generic applicability is discussed.
Keywords: 650; service science; Theory of Deferred Action; theoretical model; business process; process architecture; emergence